The black bestiary a phantasmagoria of monsters and myths from the Philippines - Hontiveros, Dave; Tan, Budjette (Tuttle Publishing, an imprint of Periplus Editions (HK) Ltd., 2022)
"How to train a Filipino dragon and other real-life adventures of three modern monster hunters! Since The Lost Journal of Alejandro Pardo was published, other creature hunters have come out of the woodwork to share their spine-tingling accounts of more discoveries. True? Exaggerated? Out-and-out lies? Read on and decide for yourself! The Black Bestiary adds to the list of powerful and fearsome supernatural creatures we met in The Lost Journal of Alejandro Pardo. Three modern creature hunters--RJ, Gus and Stanislav, who draw their inspiration from Pardo's work--relate their own chilling encounters with the sinister monsters that live among us. In this book, you'll come face-to-face with: The Bungisngis --You've heard of the Cyclops; this is a Cyclops on steroids! The Tahamaling --Never hunt in the forest without permission from these maidens! The Tiktik-- Part avian, part human, part something else. These terrifying creatures feed on the unborn. And many more creatures of horrifying aspect and predilection! You'll also discover excerpts from the journal of a certain Mr. Kolya, a contemporary of Pardo's, who always tells it like it was. Though these new sightings are all recent, the weapons used against them rely on tried-and-true magic--because forearmed, as well as forewarned, is always best! The Black Bestiary is a lively romp through the world of the imagination, as well as a great way to learn more about Asian folklore, magic and myth"--Provided by publisher.